A coupled wave-current-structure study for a floating offshore wind turbine platform - Li, Xiang; Xiao, Qing; Gonçalves, Rodolfo T.; Peyrard, Christophe (ASME, 2022)
In the present study, the influence of ocean conditions, in the combination of wave and current, on the dynamic response of the OC4 semi-submersible platform is numerically studied. The present work is inspired by the recent observations that the presence of current incidence usually induces the vortex-induced motions (VIM) phenomenon of multi-monocolumn platforms, while wave often leads to large inertia force on it. The integration of wave and current may further cause a more complex flow field around the structure than that only wave or current exists. Such VIM is not desirable considering its impact on the fatigue life of the riser, umbilical, and mooring system of the offshore structure due to the resonance behaviour of the VIM. A computational fluid dynamic (CFD) method is adopted to conduct a real-time simulation of the platform’s motion response. The tool is based on an open-source code library OpenFOAM. The results are validated against experiments with current-only conducted in the wave tank. The flow field around the platform and its impact on the structure motion and loading response are studied for a wide range of wave and current conditions. With the given incident waves, the VIM is mitigated for most cases, for a wide range of reduced velocity. This result is of practical interest for the design of FOWT, as VIM are not captured by industrial aero-hydro-mechanical models.